Automatic Continuity on Fundamental Locally Multiplicative Topological Algebras: M. R. Omidi, Ali Farajzadeh, E. Soori, B. Olfatian Gillan - Team, Support (Thai Journal of Mathematics, 2019)
In this paper we prove some results about a new class oftopological algebras namely fundamental and fundamental locally mul-tiplicative topological algebras (abbreviated by FLM). Then we presentessential results about FLM algebras. We also obtain some results onthe automatic continuity of homomorphisms between FLM algebras.